2021
DOI: 10.3389/fpubh.2021.669179
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sensitization Program on Occupational Health Hazards for Nursing and Allied Health Care Workers in a Tertiary Health Care Setting

Abstract: Background: Occupational health hazard pertaining to health care providers is one of the neglected areas that need serious attention. Any compromise in their safety would result in reduction in workforce, which may affect patient care, keeping in mind the wide gap between the required number and actual health care workers (HCWs) available in the world over.Aim: This study was undertaken to evaluate the change in knowledge through a sensitization training program on occupational health hazards and vaccination f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Okaro et al (2010) revealed that radiation monitoring and training of radiologists and radiographers provide increasing awareness of safety measures thereby enable the use of protective devices. The result of this finding is in agreement with studies of Naithani et al (2021) that workers who have received training yearly are 5.3 times more likely to be currently educated about the job and comply with protocols of safety in the laboratory. In Nigeria, studies of Salama et al (2016) specified that good proportion of radiation workers (50%) who utilizes safety devices during x-ray proceedings are less likely to be exposed to radiations as compared with others who do not use those devices for safety reasons.…”
Section: Training and Safety Practicessupporting
confidence: 89%
See 1 more Smart Citation
“…Okaro et al (2010) revealed that radiation monitoring and training of radiologists and radiographers provide increasing awareness of safety measures thereby enable the use of protective devices. The result of this finding is in agreement with studies of Naithani et al (2021) that workers who have received training yearly are 5.3 times more likely to be currently educated about the job and comply with protocols of safety in the laboratory. In Nigeria, studies of Salama et al (2016) specified that good proportion of radiation workers (50%) who utilizes safety devices during x-ray proceedings are less likely to be exposed to radiations as compared with others who do not use those devices for safety reasons.…”
Section: Training and Safety Practicessupporting
confidence: 89%
“…Adejumo et al (2012) in their study illustrated that workers who have up to five years of work experience are less likelihood to suffer for the effects of occupational hazards and would be able to comply with safety measures. Naithani et al (2021) revealed that work experience helps to improve the level of knowledge of safety measures hence reduce the chance of exposure to occupational hazards. The compliance with safety practices or measure were affected due to work inexperience, non-availability of protective equipment, lack of quarterly training among others.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of this program on the knowledge of biological hazards was highest and for the radiation, and chemical hazards were lowest. The participants of the recent study suggested that psychosocial hazards should be added to educational programs [ 29 ]. In the present study, psychosocial hazards were also considered.…”
Section: Discussionmentioning
confidence: 99%